TINGKAT EKSPLOITASI IKAN ENDEMIK BONTI-BONTI (PARATHERINA STRIATA) DI DANAU TOWUTI - Nasution, Syahroma Husni (Perhimpunan Biologi Indonesia, 2011)
ABSTRACTThe Exploitation Rate of Endemic Bonti-bonti (Paratherina striata) in Towuti Lake. Bonti-bonti(Paratherina striata) is an endemic fish species as vulnerable species to extinction. This fish livein Towuti and Mahalona Lake the tectonic-oligotrophic lakes that are located in Malili Complex,South Sulawesi. This lake is used for various purposes i.e. hydroelectric power plant, capturefishery, navigation, ecotourism and source of water for domestic uses. This lake also supports lifeof endemic fish species that should be protected from decreasing population due to intensiveexploitation. The objective of this research was to study the exploitation rate of Bonti-bonti asconservation efforts. The study was done in Towuti Lake from May 2006 to April 2007 usingdescriptive method. Utilization rate of Bonti-bonti stocks in Towuti Lake indicated an overfishingcondition of male and female population. Increasing effort (units/month) of dipnet tends to reducefishing gear productivity.Key words: exploitation rate, Bonti-bonti, endemic fish and Towuti Lake